2017
DOI: 10.1208/s12249-017-0769-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual Activity of Hydroxypropyl-β-Cyclodextrin and Water-Soluble Carriers on the Solubility of Carvedilol

Abstract: Carvedilol (CAR) is a non-selective α and β blocker categorized as class II drug with low water solubility. Several recent studies have investigated ways to overcome this problem. The aim of the present study was to combine two of these methods: the inclusion complex using hydroxypropyl-β-cyclodextrin (HPβCD) with solid dispersion using two carriers: Poloxamer 188 (PLX) and Polyvinylpyrrolidone K-30 (PVP) to enhance the solubility, bioavailability, and the stability of CAR. Kneading method was used to prepare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
4
9
0
Order By: Relevance
“…The chemical reactions that ensued between the inclusion complex and PVP culminated in a decrease in the mass of the compounds. These results are consistent with an earlier report 53 . The various SD PVP solid dispersions had lower peak intensities due to the interactions among the major compounds (ie, NMD, KD, and PVP).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The chemical reactions that ensued between the inclusion complex and PVP culminated in a decrease in the mass of the compounds. These results are consistent with an earlier report 53 . The various SD PVP solid dispersions had lower peak intensities due to the interactions among the major compounds (ie, NMD, KD, and PVP).…”
Section: Resultssupporting
confidence: 93%
“…In the case of PBS, a 19‐fold increase was observed. Several experimental studies have shown similar trends 53 . The relative increase in the dissolution of the ternary systems could be due to its amorphous nature, which has been confirmed by the XRD, DSC, and FTIR study 57 .…”
Section: Resultssupporting
confidence: 57%
“…This hypothesis is also supported by the difference between the dissolution behavior of CAR‐ASD/CA50 and PM of CAR‐ASD + CA. In the previous reports, solid dispersion systems for CAR have been reported with use of cyclodextrins, porous silica and polyvinylpyrrolidone as carrier materials of solid dispersion (Sharma et al, ; Yuvaraja & Khanam, ; Zoghbi, Geng, & Wang, ). Cyclodextrins has been widely used for the solubility enhancement due to its high solubilization potency; however, it could have the toxic potential to induce tissue irritation and cytotoxicity in gastrointestinal tract after oral administration (Irie & U. K., ).…”
Section: Resultsmentioning
confidence: 99%
“…It can self‐assemble into micelles in an aqueous solution because of its amphiphilic nature, where the hydrophobic chain can reserve the drug and the hydrophilic chain acts as a bridge connecting the drug and the aqueous medium. The micelles formed had advantages of high drug loading and excellent physical stability …”
Section: Introductionmentioning
confidence: 99%
“…The micelles formed had advantages of high drug loading and excellent physical stability. [17,18] In our design, BAI-loaded HS15/F68 mixed micelles (BAI-M) were prepared by thin-film dispersion method ( Figure 2), and the formulation was optimized with the central composite design (CCD) response surface method. The morphology, particle size and zeta potential of the optimized preparation were characterized by transmission electron microscopy (TEM) and dynamic light scattering.…”
Section: Introductionmentioning
confidence: 99%